Regulation of Drosophila trpl channels by immunophilin fkbp59. - Goel, M.; Garcia, R.; Estacion, M.; Schilling, W.P. (Journal of Biological Chemistry, 2001)
Transient receptor potential and transient receptor potential-like (TRPL) are Ca(2+)-permeable cation channels found in Drosophila photoreceptor cells associated with large multimeric signaling complexes held together by the scaffolding protein, INAD. To identify novel proteins involved in channel regulation, Drosophila INAD was used as bait in a yeast two-hybrid screen of a Drosophila head cDNA library. Sequence analysis of one identified clone showed it to be identical to the Drosophila homolog of human FK506-binding protein, FKBP52 (previously known as FKBP59). To determine the function of dFKBP59, TRPL channels and dFKBP59 were co-expressed in Sf9 cells. Expression of dFKBP59 produced an inhibition of Ca(2+) influx via TRPL in fura-2 assays. Likewise, purified recombinant dFKBP59 produced a graded inhibition of TRPL single channel activity in excised inside-out patches when added to the cytoplasmic membrane surface. Immunoprecipitations from Sf9 cell lysates using recombinant tagged dFKBP59 and TRPL showed that these proteins directly interact with each other and with INAD. Addition of FK506 prior to immunoprecipitation resulted in a temperature-dependent dissociation of dFKBP59 and TRPL. Immunoprecipitations from Drosophila S2 cells and from fly head lysates demonstrated that dFKBP59, but not dFKBP12, interacts with TRPL in vivo. Likewise, INAD immunoprecipitates with dFKBP59 from S2 cell and head lysates. Immunocytochemical evaluation of thin sections of fly heads revealed specific FKBP immunoreactivity associated with the eye. Site-directed mutagenesis showed that mutations of P702Q or P709Q in the highly conserved TRPL sequence (701)LPPPFNVLP(709) eliminated interaction of the TRPL with dFKBP59. These results provide strong support for the hypothesis that immunophilin dFKBP59 is part of the TRPL-INAD signaling complex and plays an important role in modulation of channel activity via interaction with conserved leucyl-prolyl dipeptides located near the cytoplasmic mouth of the channel.